2023
DOI: 10.3390/vaccines11091509
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of Vitamin D and Vitamin A Levels on the Response to COVID-19 Vaccine

Hassan M. Kofahi,
Baha’ R. Badran,
Refat M. Nimer
et al.

Abstract: COVID-19 vaccines were developed at an unprecedented speed in history. The factors affecting the response to COVID-19 vaccines are not clear. Herein, the effects of vitamin D and vitamin A (retinol) levels on the response to the BNT162b2 vaccine were explored. A total of 124 vaccine recipients were recruited from the general population attending vaccination centers in Irbid, Jordan. Blood samples were collected immediately before receiving the first vaccine dose (D0) and three weeks later (D21). Baseline (D0) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 77 publications
2
4
0
Order By: Relevance
“…We observed both quantitative and qualitative differences in antibody responses based on micronutrient status. Notably, no significant association was observed between circulating micronutrient concentrations and binding affinity of anti‐SARS‐CoV‐2 IgG antibodies, which was aligned with previous studies 16,22,24,25 . These findings suggested that micronutrients might not be pivotal factors in enhancing the long‐term protection provided by inactivated COVID‐19 vaccine in adults with optimal nutritional status.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We observed both quantitative and qualitative differences in antibody responses based on micronutrient status. Notably, no significant association was observed between circulating micronutrient concentrations and binding affinity of anti‐SARS‐CoV‐2 IgG antibodies, which was aligned with previous studies 16,22,24,25 . These findings suggested that micronutrients might not be pivotal factors in enhancing the long‐term protection provided by inactivated COVID‐19 vaccine in adults with optimal nutritional status.…”
Section: Discussionsupporting
confidence: 85%
“…Unlike iron and zinc, serum concentrations of fat‐soluble vitamins (A, D, and E) in our study displayed no significant association with either vaccine‐specific antibody binding affinity or neutralizing ability against SARS‐CoV‐2 virus. This aligns with some existing research on COVID‐19 vaccination, 21‐25 but contrasts with others reporting positive associations between vitamin D and antibody responses 18‐20 . These discrepancies might stem from variations in study populations, including pre‐existing vitamin D status, vaccination schedules (primer vs. booster dose), vaccine type (inactivated vs. mRNA), and even participant age 23,24 .…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations